Platform cooperatives in the sharing economy: How market challengers bring change from the margins - Aleksandrina Atanasova; Giana M. Eckhardt; Mikko Laamanen (Journal of the Academy of Marketing Science, 2024)
The now-mature sharing economy has not delivered on its original utopian promises. Instead of providing prosocial benefits for consumers and society, incumbent platforms dominate monopolistic markets. In this article, we study a novel business model in the sharing economy––the platform cooperative––to ask how can a responsible marketing strategy can be viable and effective for market challengers. We draw on a qualitative, ethnographic study of the lived experiences of consumers and managers in leading platform cooperatives Fairbnb and Drivers Cooperative, and find that while challengers cannot overhaul the system, they can engender change from the margins . We identify three dimensions of a change from the margins strategy in decentralizing the marketplace , shaping authentic narratives , and building institutional partnerships . We discuss implications of a responsible marketing strategy for market incumbents and challengers within the sharing economy and beyond, and for theorizing new frameworks in the marketing strategy literature.
Keywords: 330; Marketing strategy; Social marketing; Platform economy; Sharing economy; Platform cooperative